Rutin ameliorates glycemic index, lipid profile and enzymatic activities in serum, heart and liver tissues of rats fed with a combination of hypercaloric diet and chronic ethanol consumption - Chuffa, Luiz Gustavo A. [UNESP]; Fioruci-Fontanelli, Beatriz A. [UNESP]; Bordon, Juliana G. [UNESP]; Pires, Rafaelle B.; Braga, Camila P. [UNESP]; Seiva, Fábio R. F.; Fernandes, Ana Angélica H. [UNESP] (My University, 2014)
Alcoholism and obesity are strongly associated with several disorders including heart and liver diseases. This study evaluated the effects of rutin treatment in serum, heart and liver tissues of rats subjected to a combination of hypercaloric diet (HD) and chronic ethanol consumption. Rats were divided into three groups: Control: rats fed a standard diet and drinking water ad libitum; G1: rats fed the HD and receiving a solution of 10% (v/v) ethanol; and G2: rats fed the HD and ethanol solution, followed by injections of 50 mg/kg-1 rutin as treatment. After 53 days of HD and ethanol exposure, the rutin was administered every three days for nine days. At the end of the experimental period (95 days), biochemical analyses were carried out on sera, cardiac and hepatic tissues. Body weight gain and food consumption were reduced in both the G1 and G2 groups compared to control animals. Rutin effectively reduced the total lipids (TL), triglycerides (TG), total cholesterol (TC), VLDL, LDL-cholesterol and glucose levels, while it increased the HDL-cholesterol in the serum of G2 rats, compared to G1. Although rutin had no effect on total protein, albumin, uric acid and cretinine levels, it was able to restore serum activities of alkaline phosphatase (ALP), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatine kinase (CK) in animals fed HD and receiving ethanol. Glycogen stores were replenished in both hepatic and cardiac tissues after rutin treatment. Moreover, rutin consistently reduced hepatic levels of TG and TC and cardiac AST, ALT and CK activities. Thus, rutin treatment was effective in reducing the risk factors for cardiac and hepatic disease caused by both HD and chronic ethanol consumption.
Keywords: Ethanol; Heart; Hypercaloric diet; Liver; Rat; Rutin